Noting Ethical AI within Legal Framework: Perspectives From Indonesia (Universitas Terbuka, 2025)
As the development of technology in economic activities continue to forget ethical aspect, especially when carrying out economic activities in Indonesia, the problem of how ethics and its manifestations should be outlined in the legislative system that usually bias in the definition of discrimination or legal treatment continue to be an issue that must be seriously considered. In an effort to find the legal aspects of ethics, experts and academics start with fundamental questions such as what is meant by justice, utility, compatibility, abilities, egalitarianism, ideals, discrimination, etc. This this study is qualitatively researched aiming to understand and explore the meaning of ethics in digital economy activities, especially in the context of the use of artificial intelligence (AI). A holistic approach using complex interrelationship between various elements of ethics devinition, legal regulation, and technology to identify and analyze various dimensions of values in morality, transparency, and justice. The result shows that although AI has currently been enjoyed in Indonesia to perform tasks and used to enhance human capabilities, critical gaps in Indonesia’s current laws are found wihin the absence of transparency requirements for AI systems and weak enforcement of data protection. Therefore, it is argued to have risk-based regulatory approach tailored to cultural context of collectivism and propose policy measures, including public awareness campaigns and algorithmic impact assessments.